Rare and novel variant load threshold for KIF7, GJA1 and PDE1C genes elevates the risk of severity of congenital heart defects in Down syndrome - Agnish Ganguly; Samudra Pal; Srilagna Chatterjee; Madhusudan Das; Sumantra Sarkar; Sujay Ghosh (PLoS ONE, 2025)
Individuals with Down syndrome (DS) exhibit a higher incidence of congenital heart defects (CHD). The objective of the present study was to investigate ethnicity-specific genetic variants that increase the risk of CHD in children with DS from the Indian Bengali population. We conducted whole exome sequencing of the genomes of Down syndrome children with and without CHD and subsequently tested the identified variants in a larger cohort (N = 1798). Our findings revealed two rare variants, KIF7 rs138354681 and GJA1 rs778110855, as well as one novel variant, PDE1C PP785745, present in children with DS and CHD but absent in those without CHD. In-silico analyses indicated that these variants are pathogenic. The frequencies of the heterozygous genotypes for KIF7 rs138354681, GJA1 rs778110855, and PDE1C PP785745 were recorded as 0.027, 0.016, and 0.032, respectively. Among the 31 carriers identified, 18 individuals exhibited two variants, while four were found to have three co-occurring variants. The majority of these individuals required surgical intervention for correction, in contrast to single variant carriers, of whom only three out of nine needed surgeries. A polygenic risk score analysis revealed higher score to be significantly associated with both the presence of multiple variants and the subsequent need for surgical correction. We hypothesise that the synergistic effects of multiple variants heighten the severity of CHD, particularly in cases of ventricular septal defects, thereby necessitating surgical correction. These findings significantly enhance our understanding of the unique population-specific aetiology of CHD and the basis for the severity of its clinical presentation in individuals with Down syndrome.